Bone-conserving radiation-free intramedullary nail removal technique: A prospective surgical study on 108 patients with healed tibia fractures - Nishit Palo,; Malik, Chhavi; Shukla, Abhishek; Narayan Choudhary, Govind; Veerendra Mannan,; Rakesh Kumar G, (Asian Journal of Medical Sciences, 2023)
Background: While attempting hardware removal, intraoperative challenges and hardware removal strategy vary in each case. Only a few nail removal techniques are reported in the literature. Surgeon’s understanding and resolution of these rather challenging situations improve with experience and exposure. Patients having healed tibia fracture with in-situ intramedullary nail were subjected to intramedullary nail removal. Aims and Objectives: The aim of this study was to assess the performance of novel bone-conserving C-arm-free technique of intramedullary nail removal and describe trends such as surgical timing, complications, hardware removal ratio, intraoperative fluoroscopy requirement, comorbidities, and time since the first surgery in patients undergoing the surgical procedure. Materials and Methods: This was a prospective therapeutic observational study conducted from July 2017 to December 2021. Patients having healed tibia fracture with in-situ intramedullary nail were subjected to hardware removal using a novel bone-conserving radiation-free technique. Results: Among 108 patients, 49.72 (%) were men and 50.28 (%) were women. Patient demographics: age-45 years (mean); range-18–75 years. The overall surgical timing was 117.5±2.1 min (mean/S.D). Hypertension was the most common comorbidity overall with the incidence of 32.40% (35/108 patients); maximum 50% in the age group of 46–60 years (12/24 patients). Nail retrieval was possible in all cases with a 100% hardware removal ratio. The most common complication encountered was DVT/Thrombii (7.40%, 8/108 patients), followed by surgical site infection (5.55%, 6/108 patients) and fractures (2.77, 3/108 patients), with maximum complications in the age group of 61–75 years (63.63%, 7/11 patients). Patients presented 3.8±1.1 years (mean/SD) after the first surgery for nail removal. Conclusion: In complicated situations, an extra bony window over interlocking bolt slots can be used to maneuver the nail, thus facilitating tibial or femoral nail delivery.